2015
DOI: 10.1038/srep13882
|View full text |Cite
|
Sign up to set email alerts
|

Increase in dicentric chromosome formation after a single CT scan in adults

Abstract: Excess risk of leukemia and brain tumors after CT scans in children has been reported. We performed dicentric chromosome assay (DCAs) before and after CT scan to assess effects of low-dose ionizing radiation on chromosomes. Peripheral blood (PB) lymphocytes were collected from 10 patients before and after a CT scan. DCA was performed by analyzing either 1,000 or 2,000 metaphases using both Giemsa staining and centromere-fluorescence in situ hybridization (Centromere-FISH). The increment of DIC formation was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 25 publications
(37 reference statements)
3
31
2
Order By: Relevance
“…We recently showed that DIC formation increases significantly in PB lymphocytes after a single CT scan (5.78–60.27 mSv: mean 24.24 mSv) ( Supp. Table 1A and 1B ) [ 11 ]. We therefore recommended that 2000 or more metaphase figures in Giemsa-stained samples, and 1000 or more metaphase figures in Centromere-FISH be analyzed by DCAs in studies of low-dose radiation exposure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that DIC formation increases significantly in PB lymphocytes after a single CT scan (5.78–60.27 mSv: mean 24.24 mSv) ( Supp. Table 1A and 1B ) [ 11 ]. We therefore recommended that 2000 or more metaphase figures in Giemsa-stained samples, and 1000 or more metaphase figures in Centromere-FISH be analyzed by DCAs in studies of low-dose radiation exposure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1A and 1B ) [ 11 ]. We therefore recommended that 2000 or more metaphase figures in Giemsa-stained samples, and 1000 or more metaphase figures in Centromere-FISH be analyzed by DCAs in studies of low-dose radiation exposure [ 11 ]. DICs and chromosome translocations are produced in about an equal ratio in human PB cells after exposure to radiation [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important application of the method is in the refinement of dicentric chromosome assay (DCA), the gold standard for biodosimetry assessment of individuals after exposure to radiation [ 29 ]. The International Atomic Energy Agency recommends an analysis of more than 1000 cells for better ascertainment of dicentric chromosome formation for low radiation dose of less than 100 mSv, equivalent to a computed tomography (CT) scan [ 30 , 31 ]. A recent study by Abe et al [ 31 ] reported that the analysis of 1000 metaphase spreads probed with cenFISH was sufficient to yield comparable precision to 2000 conventional Giemsa stained metaphases.…”
Section: Resultsmentioning
confidence: 99%
“…The International Atomic Energy Agency recommends an analysis of more than 1000 cells for better ascertainment of dicentric chromosome formation for low radiation dose of less than 100 mSv, equivalent to a computed tomography (CT) scan [ 30 , 31 ]. A recent study by Abe et al [ 31 ] reported that the analysis of 1000 metaphase spreads probed with cenFISH was sufficient to yield comparable precision to 2000 conventional Giemsa stained metaphases. However, these DCA methods only assess for the occurrence of a dicentric chromosome based on the presence of primary constrictions and centromere DNA, therefore, not providing any information on whether the affected chromosome contains one or two active centromeres which may have impacts on downstream genome instability.…”
Section: Resultsmentioning
confidence: 99%